New EHR certification requirements and their association with duplicate tests and images. (27th May 2022) - Pylypchuk, Yuriy; Johnson, Christian
Abstract: Background: Certified electronic health record (EHR) technology has been adopted by most hospitals and health care providers. In 2015, the Office of the National Coordinator for Health Information Technology (ONC) published new EHR certification requirements, known as the 2015 Edition. To date, no research has examined the impact of hospitals' adoption of the 2015 Edition on health care delivery. Methods: We analyzed aggregated, longitudinal data drawn from a repository of deidentified health insurance claims collected by FAIR Health, the repository was estimated to represent about 75% of the privately insured in the United States. These data were linked with the American Hospital Association (AHA) Information Technology Supplement Survey to obtain hospitals' health information technology characteristics. A fixed effects specification was used to assess the incidence of duplicate testing and imaging in both inpatient and outpatient settings before and after the hospitals' adoption of the 2015 Edition. Results: Hospitals with the 2015 Edition were less likely to perform duplicate imaging for inpatients by 5 percentage points (or 50% from baseline). Hospitals that adopted the 2015 Edition and actively engaged in interoperable data exchange were even less likely to perform duplicate lab tests. Conclusions: Adoption of the 2015 Edition certified EHR was negatively associated with the incidence of lab and imaging test duplication in both the outpatient and inpatient settings. However, the results were not robust across specifications. Given that multiple factors influence care delivery decisions, improvements in certification standards alone are unlikely to eliminate unneeded duplicate lab and imaging tests.